Half of the patients with chest pain that are urgently referred are transported in unsafe conditions. - Bruyninckx, R; Van den Bruel, A; Aertgeerts, B; Van Casteren, V; Buntinx, F (2008)
BACKGROUND: Patients with an acute coronary syndrome should be referred to hospital urgently to start reperfusion therapy as soon as possible. Owing to the risks of ventricular fibrillation and pulseless ventricular tachycardia, urgent transport should be organized under safe conditions, that is, with a defibrillator at hand. AIM: To evaluate the type of transport of patients with chest pain referred by their general practitioner (GP). DESIGN OF STUDY: Observational study. SETTING: A sentinel network of general practices in Belgium, covering almost 1.6% of the total population. PATIENTS: One thousand nine hundred and ninety-six patients with chest pain attending their GP in 2003. METHOD: Descriptive analyses reporting proportions along with their 95% confidence interval (CI). RESULTS: Male patients were referred to hospital more often than female patients: 44.9% (95% CI: 41.6-47.8) versus 36.5% (95% CI: 33.4-39.6). For patients who were referred routinely, 92.7% (95% CI: 89.1-95.2) were transported by family and neighbours, 4.8% (95% CI: 2.8-7.9) by ambulance and 2.5% (95% CI: 1.2-5.1) by GPs. For patients who were referred urgently, ambulances transported 56.9% (95% CI: 51.1-62.7), family and neighbours 36.9% (95% CI: 31.4-42.7) and the GP 6.1% (95% CI: 3.7-9.5). CONCLUSION: Almost half of the patients with chest pain who require urgent referral are transported in unsafe conditions.